Estimating bird densities in montane deserts: A methodological comparison in South Sinai, Egypt - Kadry, Mohamed; Arcilla, Nico; Goded, Sandra; Soultan, Alaaeldin (Journal of arid environments, 2021)
Montane desert birds are particularly vulnerable to population declines driven by global climate change that is accelerated at higher elevations. Providing reliable and accurate information about their populations is essential for effective conservation management plans. However, few studies have compared the effectiveness of different survey methods for birds in high altitude arid environments, particularly in the Middle East. Here, we compare the reliability and precision of two sampling methods to estimate densities for two resident bird species in Egypt's Sinai mountains, the white-crowned wheatear (Oenanthe leucopyga) and desert lark (Ammomanes deserti). We conducted surveys for both species in vegetated and unvegetated desert using fixed-width strip transects and line transects using the distance sampling approach, and employed several statistical approaches to compare density estimates. While both methods provided reliable density estimates given sufficient detections of target species, strip transects exhibited more flexibility overall for estimating cryptic and rare species, which comprise a large proportion of this and other montane desert bird communities. Strip transects also entail lower effort and costs, an important consideration given research funding constraints. We therefore recommend strip transects over distance sampling for estimating bird densities in this and other arid montane regions. •We analyze sampling methods to estimate bird densities in montane desert.•We estimate and compare densities of two bird species and habitat types.•Bird behavior, abundance, and location influence density estimates.•Many resident bird species in montane deserts tend to be rare and cryptic.•We recommend strip transect over distance sampling for montane desert birds.